PENGARUH PEMBERIAN MPASI PABRIKAN DAN MPASI LOKAL TERHADAP STATUS GIZI BAYI - Triana, Ani; Maita, Liva (JURNAL MEDIA KESEHATAN, 2019)
Nutrition improvement programs aimed at increasing the amount and quality of MP-ASI have been carried out, including the provision of MP-ASI for infants and children aged 6-24 months from poor families. In general, there are two types of MP-ASI, which is the result of factory processing or what is known as the manufacturer's MP-ASI and which is processed at home or referred to as local MP-ASI. This study aims to determine the effect of manufacturing MPASI and local MPASI on the nutritional status of infants in the working area of ​​Sidomulyo Health Center. This research was conducted through a quasy experiment research design with a series of time (time series design) that is without using the control group as a comparison. The population is babies aged 6-12 months with a sample of 15 people in the group who were given MP-ASI Manufacturing and 15 groups who were given Local MP-ASI. The results of the study the influence of Manufacturing MPASI and Local MPASI on nutritional status with pvalue = 0.548. The need for counseling about nutritional needs, training in food processing and weighing and measuring baby's height regularly